Incorporating genetic algorithm into simulated annealing based redistricting - Sim, Kwan Hua. (Faculty of Computer Science and Information Technology, 2002)
Redistricting is a process of drawing lines as a boundary, it plays an important role in the process of decision making on space and spatial allocation. In redistricting, the main problem to be solved is to find the districting plan that maximizes the value function involved. Thus, redistricting process can be characterized as a combinatorial optimization problem and considered to be computationally intractable or NP-hard problem, so getting trapped in local optimal and difficulty in obtaining the most optimal solution have became the great challenge of redistricting problem. Latest approach of solving redistricting problem using simulated annealing has shown a significant improvement with ability to escape from local optimal.